TEKNIK TERJEMAHAN DALAM MENERJEMAHKAN KATA BUDAYA DAN KUALITAS PADA NOVEL THE MIDNIGHT LIBRARY - Yatuzzuhriyyah, Ulfiyatuzzuhriyyah; Hilman, Evert Haryanto (BASIS (Bahasa dan Sastra Inggris), 2022)
This research analyzed the translation of cultural words in The Midnight Library novel. The purpose of this research is to find out the cultural words based on Newmark’s theory (1988). Which translation technique is used to translate the cultural words according to the theory of Molina and Albir (2002). Quality assessment of cultural words by using the theory Nababan (2013). This analysis used a qualitative descriptive approach to considering data of words and phrases contained in the novel. In this study, researchers used some techniques to collect and analyze data. The result showed that there were 5 types of cultural words in the novel, which were; ecology (28%), material culture (46%), social culture (8%), social organization and customs (8%) and gestures and habits (10%). There are 9 out of 18 translation techniques applied to cultural words; borrowing (38%), amplification  (10%), adaptation (6%), generalization (4%), particularization  (4%), established equivalent (26%), descriptive  (2%), reduction (6%), and variation  (4%). The cultural words included in the translation do not affect the quality of the translation. Therefore, the translation of the cultural words is of decent quality;  the translation is accurate, acceptable and readable in the target language.